Получение двухсторонних высоковольтных эпитаксиальных кремниевых p—i—n-структур методом ЖФЭ - Вакив, Н.М.; Круковский, С.И.; Тимчишин, В.Р.; Васькив, А.П. (Технология и конструирование в электронной аппаратуре, 2013)
Разработана технология выращивания двухсторонних высоковольтных кремниевых p—i—n-структур методом жидкофазной эпитаксии в едином технологическом процессе. Электрофизические параметры полученных структур позволяют изготавливать на их основе высоковольтные диоды. Розроблено технологію вирощування двосторонніх високовольтних кремнієвих p—i—n-структур методом рідиннофазної епітаксії в єдиному технологічному процесі. Електрофізичні параметри отриманих структур дозволяють виготовляти на їх основі високовольтні діоди. Silicon p—i—n-structures are usually obtained using conventional diffusion method or liquid phase epitaxy (LPE). In both cases, the formation of p- and n-layers occurs in two stages. This technological approach is quite complex. Moreover, when forming bilateral high-voltage epitaxial layers, their parameters significantly deteriorate as a result of prolonged heat treatment of active high-resistivity layer. Besides, when using diffusion method, it is impossible to provide good reproducibility of the process. In this paper a technique of growing bilateral high-voltage silicon p—i—n-structures by LPE in a single process is proposed. The authors have obtained the optimum compounds of silicon-undersaturated molten solutions for highly doped (5•1018 cm–3) contact layers: 0.4—0.8 at. % aluminum in gallium melt for growing p-Si-layers and 0.03—0.15 at. % ytterbium in tin melt for n-Si-layers. Parameters of such structures provide for manufacturing of high-voltage diodes on their basis. Such diodes can be used in navigational equipment, communication systems for household and special purposes, on-board power supply systems, radar systems, medical equipment, etc.